HIGH ALTITUDE PULMONARY EDEMA (HAPE) - khiptiyah, mariyatul; Sartono, Teguh Rahayu; Normahayu, Indrastuti; Jaya, Wiwi (Malang Respiratory Journal, 2021)
Introduction: High altitude pulmonary edema (HAPE) is one of the acute, severe, non-cardiogenic disease that could be life threatening, occurs upon either the first or subsequent exposure to high altitude. It is triggered by a shortage of oxygen after ascending high altitude. The most effective therapeutic approach for HAPE is to immediately descend from high altitude and to give oxygenation, maintaining arterial saturation over 90%, as well as letting the patient rest from strenuous physical activity. The use of portable hyperbaric chamber is also deemed effective in certain circumstance, and nifedipine can also be used to treat HAPE, even as additional treatment in condition that the patients had yet to descend and oxygenation is still not administrable. Case Report: We reported a case at Rs. Dr. Saiful Anwar, a 23-year old male with High Altitude Pulmonary Edema (HAPE). Diagnosis established from anamnesis, physical examination, and laboratory tests. Patient complained shortness of breath when climbing Mt. Semeru, in which the patient reached an altitude of 2700 mdpl in 2 days. Physical examination showed oxygen saturation 46-49% with NRBM 10 lpm, and rhonchi breath sound in all lung areas. Laboratory examination showed leukocytosis, blood gas analysis showed hypocarbia, severe hipoxemia, metabolic acidosis, and type I respiratory failure. Ches XRay showed wide, irregular infiltrate in both lungs. Based on those, the patient was diagnosed with HAPE. In this case, the patient was given oxygenation.Conclussion: In this case, the patient was diagnosed with HAPE based on anamnesis, physical examination, and laboratory tests. Oxygenation given to the patient improved his condition.Key words: High altitude disease, Acclimatization, Pathophysiology, Management and treatment